Berberine potently attenuates intestinal polyps growth in ApcMin mice and familial adenomatous polyposis patients through inhibition of Wnt signalling. Issue 11 (9th September 2013) - Zhang, Junfang; Cao, Hailong; Zhang, Bing; Cao, Hanwei; Xu, Xiuqin; Ruan, Hang; Yi, Tingting; Tan, Li; Qu, Rui; Song, Gang; Wang, Bangmao; Hu, Tianhui
Abstract As a traditional anti‐inflammatory Chinese herbal medicine, Alkaloid berberine has been recently reported to exhibit anti‐tumour effects against a wide spectrum of cancer. However, the mechanism was largely unknown. Gene chip array reveals that with berberine treatment, c‐Myc, the target gene of Wnt pathway, was down‐regulated 5.3‐folds, indicating that berberine might inhibit Wnt signalling. TOPflash analysis revealed that Wnt activity was significantly reduced after berberine treatment, and the mechanism of which might be that berberine disrupted β‐catenin transfer to nucleus through up‐regulating the expression of adenomatous polyposis coli (APC) gene and stabilized APC‐β‐catenin complex. Berberine administration in ApcMin/+ mice exhibited fewer and smaller polyps in intestine, along with reduction in cyclin D1 and c‐Myc expression. In clinical practice, oral administration of berberine also significantly reduced the familial adenomatous polyposis patients' polyp size along with the inhibition of cyclin D1 expression in polyp samples. These observations indicate that berberine inhibits colon tumour formation through inhibition of Wnt/β‐catenin signalling and berberine might be a promising drug for the prevention of colon cancer.